2020
DOI: 10.37217/tebd.583207
|View full text |Cite
|
Sign up to set email alerts
|

Manevi Şükran Ölçeği'nin Türkçe Uyarlaması Geçerlik Ve Güvenirlik Çalışması

Abstract: Öz Bu çalışmanın amacı, Hlava, Elfers ve Offringa (2014) tarafından geliştirilen Manevi Şükran Ölçeği'nin Türkçe adaptasyon çalışmasını gerçekleştirmektir. Bu doğrultuda ölçeğin Türkçe formunun psikometrik özellikleri incelenmiştir. Araştırmanın örneklemini toplamda 430 katılımcıdan oluşan üç ayrı örneklem grubundan oluşan katılımcılar oluşturmaktadır. Birinci örneklem grubu aracılığıyla toplanan verilerin analizi sonucunda ölçeğin dilsel eşdeğerlik çalışması gerçekleştirilmiştir. İkinci örneklem grubu aracılı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…Upon examining the criterion-related validity, the EGS' relationships with the Turkish version of the TGS (Kaplaner & Ekşi, 2020) and S-GRAT (Oğuz-Duran, 2017) resulted in significant positive relationships. Moreover, the item-total correlations and group comparisons of the upper and lower 27 percentiles were examined for analyzing the EGS' items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon examining the criterion-related validity, the EGS' relationships with the Turkish version of the TGS (Kaplaner & Ekşi, 2020) and S-GRAT (Oğuz-Duran, 2017) resulted in significant positive relationships. Moreover, the item-total correlations and group comparisons of the upper and lower 27 percentiles were examined for analyzing the EGS' items.…”
Section: Discussionmentioning
confidence: 99%
“…The TGS was developed by Hlava, Elfers, and Offringa (2014) and adapted to Turkish by Kaplaner and Ekşi (2020). It is a 16-item scale with 4 sub-dimensions and aims to measure transpersonal gratitude.…”
Section: Transpersonal Gratitude Scale (Tgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the internal consistency coefficient of the total score was reported to be 0.84. [14] Garaulet et al suggested that scores between "0-5" indicated "non-emotional eaters," scores between "6-10" indicated "low-level emotional eaters," scores between "11-20" indicated "emotional eaters," and scores between "21-30" indicated "very emotional eaters." 13 The Beck Depression Inventory was developed by Beck et al in 1961.…”
Section: Measurementsmentioning
confidence: 99%
“…Brinker ve Dozois tarafından 2009 yılında geliştirilen RDBÖ, belirli bir içerikten bağımsız olarak depresyona ek diğer sıkıntılı duygu durumları da kapsayan kontrol edilemeyen, geri-dönüşlü (recurrent) ve tekrarlayıcı özellikleri içeren genel bir ruminasyon eğilimini ölçmektedir. Türkçeye uyarlaması Karatepe (2010) tarafından uzmanlık tezi kapsamında, 350 sağlıklı gönüllü katılımcıdan oluşan bir örneklemde gerçekleştirilmiştir. Güvenirlik çalışmasında ölçeğin orijinal formu ile benzer şekilde, 20 maddeden oluştuğu ve tek faktörlü bir yapıya sahip olduğu görülmüştür.…”
Section: Ruminatif Düşünce Biçimi öLçeği (Rdbö)unclassified